Right This Way: A History of the Audience - Viagas, Robert (Rowman & Littlefield Publishers, 2023)
When you sit down at a play, movie, or concert—or even just watch TV or scroll on your phone—you are taking part in one of the oldest and most meaningful forms of behavior. Being part of an audience is a universal experience, one that has remained a constant feature of human societies even as it has evolved from colosseums to tiny glowing screens. Right This Way is a pop history of audiences through the ages. Delving into the distinctive aspects of what he calls “audiencing,” former Playbill editor Robert Viagas renders the view from the cheap seats in energetic prose. He walks us through the different types of audiences and the history of their changing behaviors, what science has to say about how our brains respond to our experiences, how technology will continue to shape audiences, and why, during COVID-19, people risked a deadly virus to be part of a crowd. Drawing on perspectives from critics, performers, scholars, and many others, Right This Way is a lively, thought-provoking meditation on the audience experience. You’ll never sit and watch something the same way again.